1999
DOI: 10.1159/000008055
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Brain MRI Lesion Volume Measurements in Multiple Sclerosis Using a Local Thresholding Technique: Effects of Formal Operator Training

Abstract: The assessment of lesion load (LL) on brain magnetic resonance imaging (MRI) scans from patients with multiple sclerosis (MS) is widely used to monitor disease evolution, natural or modified by treatments. In this study, we evaluated the effect of formal operator training on the intra- and inter-observer reproducibility of LL measurements obtained by several operators in a setting similar to that of clinical trials. Proton-density (PD)-weighted, unenhanced and enhanced T1-weighted brain MRI scans were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Central adjudication of images in other clinical circumstances has become the gold standard for this reason. [29][30][31][32][33][34][35][36][37][38] In summary, we have shown that mesalamine (800 mg) administered twice daily for 10 weeks at a dosage of 4.8 g/day is effective for induction of clinical and endoscopic remission in patients with mildly to moderately active UC. Importantly, we also show that evaluation of endoscopic eligibility criteria by a central reader has the potential to improve the efficiency of randomized controlled trials of induction therapy in UC by minimizing inclusion of patients with low endoscopic disease activity that increases placebo rates.…”
Section: Discussionmentioning
confidence: 99%
“…Central adjudication of images in other clinical circumstances has become the gold standard for this reason. [29][30][31][32][33][34][35][36][37][38] In summary, we have shown that mesalamine (800 mg) administered twice daily for 10 weeks at a dosage of 4.8 g/day is effective for induction of clinical and endoscopic remission in patients with mildly to moderately active UC. Importantly, we also show that evaluation of endoscopic eligibility criteria by a central reader has the potential to improve the efficiency of randomized controlled trials of induction therapy in UC by minimizing inclusion of patients with low endoscopic disease activity that increases placebo rates.…”
Section: Discussionmentioning
confidence: 99%
“…These operator-assisted procedures such as local thresholding have been successfully employed (7); however they require time and are indeed associated with some degree of intra and interoperator variability (8,9). Therefore, it is obvious that the development of a tool that would permit automated measurement of brain lesion load in MS is an actively pursued goal by several research groups.…”
mentioning
confidence: 99%
“…Large agreement differences often exist between operators drawing regions of interest (ROIs) of hyperintense lesions on Fluid Attenuated Inversion Recovery (FLAIR) MRI brain scans of patients with multiple sclerosis (MS) despite training and standards designed to minimize inter-operator variability [1-4]. These differences can be broken down into two categories: a) lesion outline disagreement and b) lesion detection disagreement.…”
Section: Introductionmentioning
confidence: 99%